The Impact of the KIP-K Scholarship Program and Learning Motivation on Academic Performance of Economics Education Students - Rizal Wange; Melizubaida Mahmud; Abdulrahim Maruwae; Radia Hafid; Sudirman Sudirman (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the influence of the KIP-K scholarship program policy and learning motivation on the academic achievement of students in the Economics Education Department at Gorontalo State University. The study applies a quantitative approach using survey techniques for data collection. Data processing was carried out using multiple linear regression analysis with the help of statistical software. Information was collected directly from KIP-K scholarship recipients through questionnaires distributed at Gorontalo State University. The partial results show that there is a positive influence of the KIP-K Scholarship Program Policy (X1) on Academic Achievement (Y), with a t-value of 2.626 > 1.687 and significance level of 0.012 < 0.005. Learning Motivation (X2) also has an influence with a t-value of 4.067 > 1.687 and significance level of 0.000 < 0.005. Simultaneously, the KIP-K scholarship program policy and learning motivation significantly contribute to students’ academic achievement, with an F-value of 11.581 > 2.859 and a significance level of 0.000 < 0.005. However, there are also other factors influencing academic achievement that were not the focus of this study, such as family support and environmental conditions, which account for 58.5% of the influence.